Single Laboratory Validation of Four Methods for Quantification of HMF in Honey - Elif Yıldız; Abdullah Tahir Bayraç (Journal of Advanced Research in Natural and Applied Sciences)
Hydroxymethylfurfural or 5-(hydroxymethyl)-2-furaldehyde (HMF) has been absent or found in honey naturally at very low amount. It is formed in honey mainly by heating process and improper storage conditions. HMF has been reported to have cytotoxic, carcinogenic, and mutagenic effects and thus regulatory agencies in many countries impose restrictions on its maximum levels in honey. Validated methods have been required for effective and specific detection and quantification of HMF in food samples. In this study, a single laboratory validation study was conducted on four quantification methods: direct spectral analysis, High Performance Liquid Chromatography (HPLC) analysis, Seliwanoff and Winkler methods. All methods showed linearity with the lowest R2 value of 0.992. Two method performance parameters, accuracy, and precision were satisfied by each four methods with recovery values at 98.2%, 100.2%, 102.5% and 103.3% and RSDr (relative standard deviation) % values at 6.97%, 6.19%, 2.87% and 0.90% for spectral analysis, Seliwanoff, HPLC and Winkler methods, respectively. Based on the measurement uncertainties of four quantification methods, honey samples spiked with HMF at the final concentration of 0.004mg/0.1g were reported as 0.004 mg/0.1g ± 0.00025 mg/0.1g by spectral analysis, 0.0036 mg/0.1g ± 0.000691 mg/0.1g by Seliwanoff method, 0.004 mg/0.1g ± 0.00045 mg/0.1g by HPLC and 0.0039 mg/0.1g ± 0.00022 mg/0.1g by Winkler methods (k=2, confidence level of 95%). The validated methods can quantify HMF in honey with a target concentration of 0.004 mg/0.1g, specifically and accurately.